2017
DOI: 10.1080/01419870.2017.1348530
|View full text |Cite
|
Sign up to set email alerts
|

Politicized and depoliticized ethnicities, power relations and temporality: insights to outsider research from comparative and transnational fieldwork

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The researcher also needs to reflect on factors that might affect the results of the study due to the social interaction during the interviews (see, Baser & Toivanen 2018). The interviews were conducted by the author of this article, who belongs to the majority Time of immigration to Finland 1-4 years ago (12), 5-8 years ago (9), 9-12 years ago (10).…”
Section: Some Reflections Regarding the Chosen Research Methodsmentioning
confidence: 99%
“…The researcher also needs to reflect on factors that might affect the results of the study due to the social interaction during the interviews (see, Baser & Toivanen 2018). The interviews were conducted by the author of this article, who belongs to the majority Time of immigration to Finland 1-4 years ago (12), 5-8 years ago (9), 9-12 years ago (10).…”
Section: Some Reflections Regarding the Chosen Research Methodsmentioning
confidence: 99%
“…I was able to gain access to the field and find research participants relatively easily as my positionality was constructed as a "neutral" outsider to the Kurdish community. Researcher positionality and how that potentially affected the data collection and knowledge production is discussed in more detail in Baser and Toivanen (2016), highlighting significant differences in researcher positionality based on "ethnicity" and national background (Turkish vs. Finnish).…”
Section: Methodsmentioning
confidence: 99%
“…Considering that interviews were conducted at a time in which notions of citizenship were highly politicised – the military campaign against IS was positively progressing and as an increasing portion of Iraqi territory was liberated, questions about future governance arrangements abounded among policymakers as well as the displaced population – sensitive issues were discussed with the interviewees only when raised by them. Overall, the authors found the answers on questions of citizenship to be forthright (Baser and Toivanen, 2017). The interviews have been analysed in order to detect recurrent themes expressed by the displacement population, as well as similarities and differences in the recollection of the displacement experience across ethnic and religious groups.…”
Section: Methodology and Datamentioning
confidence: 99%